Subcutaneous immunization with inactivated bacterial components and purified protein of Escherichia coli, Fusobacterium necrophorum and Trueperella pyogenes prevents puerperal metritis in Holstein dairy cows. - Vinícius Silva Machado (Public Library of Science (PLoS), 2014)
In this study we evaluate the efficacy of five vaccine formulations containing different combinations of proteins (FimH; leukotoxin, LKT; and pyolysin, PLO) and/or inactivated whole cells (Escherichia coli, Fusobacterium necrophorum, and Trueperella pyogenes) in preventing postpartum uterine diseases. Inactivated whole cells were produced using two genetically distinct strains of each bacterial species (E. coli, F. necrophorum, and T. pyogenes). FimH and PLO subunits were produced using recombinant protein expression, and LKT was recovered from culturing a wild F. necrophorum strain. Three subcutaneous vaccines were formulated: Vaccine 1 was composed of inactivated bacterial whole cells and proteins; Vaccine 2 was composed of proteins only; and Vaccine 3 was composed of inactivated bacterial whole cells only. Two intravaginal vaccines were formulated: Vaccine 4 was composed of inactivated bacterial whole cells and proteins; and Vaccine 5 was composed of PLO and LKT. To evaluate vaccine efficacy, a randomized clinical trial was conducted at a commercial dairy farm; 371 spring heifers were allocated randomly into one of six different treatments groups: control, Vaccine 1, Vaccine 2, Vaccine 3, Vaccine 4 and Vaccine 5. Late pregnant heifers assigned to one of the vaccine groups were each vaccinated twice: at 230 and 260 days of pregnancy. When vaccines were evaluated grouped as subcutaneous and intravaginal, the subcutaneous ones were found to significantly reduce the incidence of puerperal metritis. Additionally, subcutaneous vaccination significantly reduced rectal temperature at 6±1 days in milk. Reproduction was improved for cows that received subcutaneous vaccines. In general, vaccination induced a significant increase in serum IgG titers against all antigens, with subcutaneous vaccination again being more effective. In conclusion, subcutaneous vaccination with inactivated bacterial components and/or protein subunits of E. coli, F. necrophorum and T. pyogenes can prevent puerperal metritis during the first lactation of dairy cows, leading to improved reproduction.